Determinan Backlog Perumahan di Indonesia Tahun 2024 dengan Pendekatan Regresi Robust MM-Estimation - Safitri, Gita; Herwindalita, Erina (Politeknik Statistika STIS, 2025)
Home ownership backlog is still a serious problem in Indonesia, especially among low-income people. This study aims to analyze the effect of regional macro variables on the backlog of home ownership in Indonesia in 2024. The method used is robust MM-estimation regression with a unit of analysis of 38 provinces. The data used are secondary data from the BPS Statistics and the Ministry of PUPR. The independent variables include population density, Construction Cost Index (IKK), poverty rate, and unemployment rate (TPT). Based on the research results, population density, IKK and the poverty rate have a significant effect on backlog, while the unemployment rate has no significant effect. Based on the research that has been done, controlling population density and construction cost efficiency need to be prioritized in reducing backlog, as well as expanding housing subsidies for low-income people as a long-term solution.